Strategi Pengembangan Agroindustri Olahan Buah Pidada (Sonneratia Caseolaris) di Pulau Santen, Kabupaten Banyuwangi - Dini Nafisatul Mutmainah; Ahmad Haris Hasanuddin Slamet; Kirana Kusumaningrum; Dian Kumaila Dewi (LPPM Universitas Terbuka, 2022)
Mangrove fruit or known as pidada fruit has great potential to be used as a variety of processed products. The high nutritional content of pidada fruit makes it have more added value as a processed product. This study aimed to analyze the strategy for developing processed products from pidada fruit. The data used in this study consisted of primary data and secondary data. The method used to formulate a development strategy is SWOT (Strengths, Weaknesses, Opportunities, and Threats). Primary data consisted of direct observation of the potential of pidada fruit on Santen Island and data from interviews with related parties. While secondary data consisted of supporting sources from the web and journal articles. The SWOT method was used to analyze internal and external factors in product development. Based on the SWOT analysis, the Internal Factor Evaluation (IFE) matrix obtained a value of 2,682 and the External Factor Evaluation (EFE) matrix obtained a total value of 3,000. This showed that the development of the pidada fruit processed agro-industry has great potential in its development. Meanwhile the strategies that can be applied are intense market penetration, market development, and product development.